2023
DOI: 10.55544/jrasb.1.5.21
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on Anti-Ulcer Activity of Rhododendron Arboreum Flower in Wistar Rat

Abstract: Peptic ulcers, or open sores in the stomach or duodenum, can cause a great deal of discomfort. What's more, it affects a disproportionately significant percentage of people worldwide. Preliminary phytochemical study revealed that the Ethanol flower extract of Rhododendron arboretum (ELRA) is rich in Alkaloids, saponins, tannins, flavonoids, reducing sugars, and glycosides, all of which have been linked to poor dietary habits, prolonged use of nonsteroidal anti-inflammatory drugs (NSAIDs), stress, and infection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…One category of these completely natural medications is known as essential oils (EOs). In recent times, there has been a great deal of discussion on EOs [3,4]. Up to this point, we have located approximately 3,000 Eos.…”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation
“…One category of these completely natural medications is known as essential oils (EOs). In recent times, there has been a great deal of discussion on EOs [3,4]. Up to this point, we have located approximately 3,000 Eos.…”
Section: Introductionmentioning
confidence: 83%
“…Products that fulfil this requirement always come from a vegetable source, but they may have been extracted using a non-aqueous solvent or have been subjected to cold absorption. As a result, we are able to divide the commodities into four distinct categories [3]. They dissolve in ether and ethanol, but not in water; essential oils also dissolve in fixed oils, but not in water.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, GA treatment-induced AMPK activation may be responsible for the downregulation of insulin receptor substrate-1 Ser636/639, which suppresses gluconeogenesis [36], the upregulation of the SHP gene, which inhibits PEPCK and P6Pase [37], and the facilitation of transducer of regulated cAMP response element-binding protein-2, which inhibits PEPCK and G6Pase gene expression [38]. Indeed, we found that administering GA to mouse liver and hepatocytes led to an upregulation of Akt signalling [40]. Liver Akt activity is associated with maintaining normal blood sugar levels [41].…”
Section: Gallic Acidmentioning
confidence: 96%
“…However, its presence in the brain is extremely scarce in comparison to that of CB1. Nevertheless, it appears that CB2 plays a significant part in the functions of macrophages and microglia [76,77]. When microglia are activated, there is a significant rise in the expression of CB2, and activation of CB2 leads to a reduction in the synthesis of chemicals that promote inflammation [78].…”
Section: Cannabinoids and Endocannabinoids Systemsmentioning
confidence: 99%